A new theory of conscientious objection in medicine : justification and reasonability - Card, Robert F. (New York : Routledge, 2020)
"This book argues that a conscientiously objecting medical professional should receive an exemption only if the grounds of an objector's refusal are reasonable. It defends a detailed, contextual account of public reasonability suited for healthcare, which builds from the overarching concept of Rawlsian public reason. The author analyzes the main competing positions and maintains that these other views fail precisely due to their systematic inattention to the grounding reasons behind a conscientious objection; he argues that any such view is plausible to the extent that it mimics the 'reason-giving requirement' for conscience objections defended in this work. Only reasonable objections can defeat the prior professional obligation to assign primacy to patient well-being, therefore one who refuses a patient's request for a legally available, medically indicated, and safe service must be able to explain the grounds of their objection in terms understandable to other citizens within the public institutional structure of medicine. The book further offers a novel policy proposal to deploy the Reasonability View: establishing conscientious objector status in medicine. It concludes that the Reasonability View is a viable and attractive position in this debate. A New Theory of Conscientious Objection in Medicine: Justification and Reasonability will be of interest to researchers and advanced students working in bioethics, medical ethics, and philosophy of medicine, as well as thinkers interested in the intersections between law, medical humanities, and philosophy"--
Chapter 1. The Main Considerations -- 1 Introduction -- 2 What Matters: A Thought Experiment in the Real World -- 3 Setting the Stage: What are Conscience Objections? -- 4 Conscience, Conscientious Objection versus Civil Disobedience, and the Problem of Toleration and Public Reason -- 5 Reasons, Reason-Giving, and the Reasonability View -- 6 Introduction to Professional Responsibility -- 7 Moral Complicity -- Chapter 2. The Inescapability of Reasons-Assessment -- 1 Introduction -- 2 Philosophical Views: Genuineness View -- 3 Matching View -- 4 Incompatibility View -- 5 Referral View -- 6 The Reasonability View and the Inescapability of Reasons-Assessment -- 7 Some Possible Responses -- 8 Is Assessing Reasons Really Necessary? -- 9 Reasons Not to Ask for Reasons: Is Assessing Providers' Reasons Intolerant? -- 10 Conclusion -- Chapter 3. Developing the Reasonability View -- 1 Introduction -- 2 The Individual and Social Nature of Justificatory Reasons -- 3 Reasonability in Medicine and its Application to Some Core Cases -- Chapter 4. Further Developing the Reasonability View -- 1 Introduction -- 2 Objections to the Reasonability Standard -- 3 The Reasonability View and Conscientious Objection by Medical Students -- 4 The Reasonability View and Institutional Conscience -- Chapter 5. From Objections to Exemptions: Establishing Conscientious Objector Status in Medicine -- 1 Introduction -- 2 Background on Military CO Status -- 3 Military and Medical CO: Why the Existence of One Does Not Necessarily Support -- the Other -- 4 The Medical Conscientious Objector Board and the Duties of Providers Granted CO Status -- 5 Why is Establishing CO Status in Medicine an Attractive Policy Proposal? -- 6 Is Establishing CO Status in Medicine Using a Reasonability Standard Workable? Is it an Impractical Policy? -- 7 Is Utilizing CO Status as a Policy Irreparably Politically Tainted? Does this Policy Violate Rights? -- 8 Does a Policy of Medical CO Status Establish a Positive Obligation to Provide Contested Services to Patients? -- Chapter 6. Alternative Views, Objections, and Replies -- 1 The Incompatibility View v2.0 -- 2 The Market View: Should We Allow Discriminatory Conscientious Objection? -- 3 Integrity, the All-or-Nothing Problem, and the Moral Status of Medical Practices -- 4 How Much Should Reasons Matter if We Value Toleration? -- 5 Concluding Note.
OCLC-licensed vendor bibliographic record.
Keywords: Conscientious objection; Physicians -- Professional ethics; Medical ethics; Medicine -- Philosophy; PHILOSOPHY / Ethics & Moral Philosophy; MEDICAL / Ethics